The Implementation of Hygiene and Sanitation in the Dining Room Area of Yugo Restaurant, Vega Hotel Gading Serpong - Nando, Felix; Zahra, Gladys Giandi; Lawrence, Jenifer; Evelyn, Rivabel; Liementara, Viona Lovina (Corespub, 2025)
Hygiene and sanitation play a crucial role in the restaurant industry to maintain cleanliness standards. Hygiene refers to health practices that aim to maintain personal and environmental cleanliness from factors that can affect them, while sanitation is a preventive measure focusing on environmental health. The aim of this study is to examine the implementation of hygiene and sanitation at Yugo Restaurant, Vega Hotel Gading Serpong. The research uses a qualitative method with data collection techniques including observation, interviews, and documentation. The results from interviews indicate that the implementation of hygiene and sanitation at Yugo Restaurant is well-applied and in accordance with Standard Operating Procedures (SOP), which helps minimize food contamination, prevents the transmission of diseases, viruses, and bacteria that could harm customers. A good implementation of hygiene and sanitation is expected to prevent undesirable incidents and maintain the restaurant’s quality.